Gross and microanatomic description of the dental pads of the Florida manatee, Trichechus manatus latirostris, and their importance to mastication - Barboza, Meghan; Kallaway, Kiara (Archives of Oral Biology, 2024)
Objective Florida manatee feeding ecology is critical to species survival, but the role of dental pads in feeding has received limited attention. This study characterized the gross and microscopic anatomy of the manatee’s dorsal and ventral dental pad in relation to these structures’ importance in mastication, which furthers our understanding of manatee feeding and health. Design Whole heads from 6 animals (4 male and 2 female) of varying sizes were examined grossly. Sections (5 µm) from throughout the dorsal and ventral dental pads were stained with Hematoxylin and Eosin to document microanatomy. The thickness of the epithelium and stratum corneum were measured. Results The ventral dental pad epidermal (1129–3391 µm) and stratum corneum (331–1848 µm) thickness increased with increased body size. The dorsal dental pad epidermal (690–1988 µm) and stratum corneum (121–974 µm) thickness varied relative to size. The dental pad anatomy, including the thickened stratum corneum, indicates an importance similar to molars in grinding and physically breaking up plant material. Extensive appendages including filiform-like papillae and well-developed rete were observed and likely provide physical support for mastication. Conclusion While the sample size limits specific conclusions based on sex or age, it provides a good overview of the anatomy of the dental pads. The manatee is the only mammal known to have a ventral dental pad and the well-developed grinding surfaces demonstrates a crucial role in mastication for these structures. These dental pads should be evaluated during health checks and necropsies and considered in future research on manatee’s feeding mechanisms.
Keywords: Dental pad; Florida manatee; Hard palate; Keratinization; Mastication; Stratum corneum; dept.bio; peer-reviewed